CHARACTERISTICS OF NORMAL CONCRETE USING AGGREGATE LATERITE SAND AND FLY ASH AS AN INGREDIENT ADDED - GAILEA, WANDI (KURVA S JURNAL MAHASISWA, 2014)
Thesis civil engineering Faculty departements unversitas 17 August 1945 samarinda.Normal concrete is concrete has a bulk density 2200-2500 kg/má¶¾ using coarse aggregate laterite rupture or without at rupture.Concrete material is a mixture of fly ash added plus fly ash concrete, generally in the form of particles-particles of added material can be any admixture of asbestos fibers, plastic fibers polypropylene, or a piece of steel wir. Fly ash in concrete works to improve the workability of cement and reduced water consumption. That makes concrete more ductile than ordinary concrete. The purpose of thi study to compare the compressive strength at yield normal concrete and concrete using fly ash added materials and coarse aggregate of laterite red soil and fine aggregat from the red earth samarinda northThis study uses a mixture of national standard design method Indonesia 03-2847-2002 conducted in the laboratory using the maximum size of coarse aggregat is 30 mili-meters samples used for normal concrete and concrete material variation plus 5% and 10% respectively variation using 30 samples and the total number of samples is 90 samples From the test results normal concrete compressive strength at 28 days compressive strength value of the average - average need (f'cr) is 101.528 and the compressive strength required (f'c) is 86.95 kg / cm2 of the average compressive strength needs to be targeted right (f'cr) = 205 kg / cm2 and the compressive strength which hinted (f'c) = 125 kg / cm2. Materials testing concrete compressive strength of fly ash added 5% at 28 days the compressive strength average in the target (f'cr) was 110.47 kg / cm2 and the compressive strength which hinted (f'c) is 98.01 kg / cm2 of the average compressive strength - need targeted average (FCR) = 205 kg / cm2 and the compressive strength which hinted (f'c) = 125 kg / cm2. Concrete compressive strength testing of materials plus 10% fly ash pad aumur 28 days the compressive strength average (f'cr) was 118.07 kg / cm2 and the compressive strength required (f'c) is 98.26 kg / cm2 of compressive strength of the average - average need are on target (f'cr) = 205 kg / cm2 and the compressive strength which hinted (f'c) = 125 kg / cm2.